Effect of Customer Relationship Management Strategy on Customer Loyalty in The Insurance Sector in Kenya (British Journal of Multidisciplinary and Advanced Studies, 2024)
It remains a challenge to understand the effect of target marketing and customer service delivery on customer loyalty given limited empirical evidence on the effect of customer relationship management strategy on customer loyalty within the Kenyan insurance industry is limited. The study aimed at determining the effect of customer relationship management strategy on customer loyalty in the insurance sector in Kenya. Specifically, the study sought to find out the effect of customer interaction, target marketing, customer service delivery and loyalty programs on customer loyalty in the insurance industry in Kenya. A descriptive research design was adopted with quantitative approaches. The study targeted 204 insurance brokers from which 135 firms were sampled using a simple random sampling method. Data was collected from 84 marketing managers representing the brokerage firms using a semi-structured questionnaire. Both descriptive (mean, standard deviation, percentages) and inferential (correlation and regression) data analysis were adopted to estimate results with the aid of SPSS. Findings indicate that customer loyalty programs, target marketing and customer interactions positively influences customer loyalty in the insurance industry. Nevertheless, customer service delivery has a negative influence on customer loyalty in the Kenya’s insurance industry. The study’s conclusion was that target marketing and customer loyalty programs have a positive effect on customer loyalty within the Kenya’s insurance industry. This study recommends that insurance companies should adopt customer relationship management as this has a positive effect on customer loyalty.